Digoxin Combined with Aerobic Interval Training Improved Cardiomyocyte Contractility - Abreu, Gabriel Vasconcelos; Claudio, Erick Roberto Gonçalves; Aguiar, Andreo Fernando; Giordani, Morenna Alana; de Queiroz, Eveline Aparecida Isquierdo Fonseca; Lima-Leopoldo, Ana Paula; Leopoldo, André Soares; Sugizaki, Mário Mateus (International Journal of Sports Medicine, 2020)
Digoxin is a cardiotonic that increases the cardiac output without causing deleterious effects on heart, as well as improves the left ventricular performance during physical exercise. We tested whether the association between chronic digoxin administration and aerobic interval training (AIT) promotes beneficial cardiovascular adaptations by improving the myocardial contractility and calcium (Ca2+) handling. Male Wistar rats were randomly assigned to sedentary control (C), interval training (T), sedentary digoxin (DIGO) and T associated to digoxin (TDIGO). AIT was performed on a treadmill (1h/day, 5 days/week) for 60 days, consisting of successive 8-min periods at 80% and 20% of VO2máx for 2 min. Digoxin was administered by orogastric gavage for 60 days. Left ventricle samples were collected to analysis of Ca2+ handling proteins; contractility and Ca2+ handling were performed on isolated cardiomyocytes. TDIGO group had a greater elevation in fractional shortening (44%) than DIGO, suggesting a cardiomyocyte contractile improvement. In addition, T or TDIGO groups showed no change in cardiomyocytes properties after Fura2-acetoxymethyl ester, as well as in sarcoplasmic reticulum Ca2+-ATPase (SERCA2a), phospholamban and calcineurin expressions. The main findings indicate that association of digoxin and aerobic interval training improved the cardiomyocyte contractile function, but these effects seem to be unrelated to Ca2+ handling.
Keywords: digoxin; calcium; contractility; aerobic interval training